(untitled) (Latakia University Journal -Medical Sciences Series, 2021)
Background: Megaloblastic Anemia is a relatively common disease, mainly caused by folic acid and vitamin B12 deficiency. Identification of the underlying cause is important in the diagnosis of vitamin B12 deficiency. Helicobacter pylori is one of the most common causes of peptic ulcer disease worldwide and a major cause of chronic gastritis leading to atrophy of gastric glands. It is suggested that there may be a casual relationship between H. pylori and vitamin B12 deficiency. Aim: The relationship of H. pylori infection with B12 deficiency anemia . The relationship of gastrointestinal appearance (gastritis) to B12 deficiency anemia. Materials and Methods: This was a prospective case – control study involving 60 newly diagnosed megaloblastic anemia patients at Hematology Unit, Internal Medicine Department, Tishreen University Hospital, Lattakia, during the period between December 2019 – December 2020. Control group consisted of 60 patients without megaloblastic anemia. Both patients and control groups underwent upper gastrointestinal endoscopy, with simultaneous test of H. Pylori stool antigen. Biopsies were taken from the gastric antrum and corpus by separate sterile forceps in each site. These biopsies were studied for H. pylori infection, as well as the level of gastritis and gastric atrophy. Results: Out of 60 patients, 43 were male and 17 were female. Mean age of patients was 45.6 ± 6.7 years. All the patients of the study had macrocytosis on peripheral smear. Helicobacter pylori was detected in 21 (35%)of 60 patients with megaloblastic anemia, and in 26 (43.3%) of 60 control. In both groups, serum vitamin B12 levels were significantly lower in patients with H.pylori positive than in those with H.pylori negative. Conclusion: Helicobacter pylori seems to be a causative agent in the development of adult vitamin B12de-ficiency.